2002
DOI: 10.1080/07391102.2002.10506840
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of BIV TAR-Tat: Models of Peptide Binding

Abstract: A new approach in determining local residue flexibility from base-amino acid contact frequencies is applied to the twelve million lattice chains modeling BIV Tat peptide binding to TAR RNA fragment. Many of the resulting key features in flexibility correspond to RMSD calculations derived from a set of five NMR derived structures (X. Ye, R. A. Kumar, and D. J. Patel, Protein Data Bank: Database of three-dimensional structures determined from NMR (1996)) and binding studies of mutants (L. Chen and A. D. Frankel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The reasoning behind this is the absence of side chain optimization, where we assumed the same lattice contact frequencies for all types of Tat species. This contact map also confirmed that our newly rewritten code generates the identical output as the former program, thus validating our approach(Hsieh, M.; Lustig, B. San Jose State University. Unpublished Data.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…The reasoning behind this is the absence of side chain optimization, where we assumed the same lattice contact frequencies for all types of Tat species. This contact map also confirmed that our newly rewritten code generates the identical output as the former program, thus validating our approach(Hsieh, M.; Lustig, B. San Jose State University. Unpublished Data.…”
supporting
confidence: 79%
“…In this thesis, the BIV TAR RNA and Tat peptide sequences were adapted from Puglisi, and other groups (Puglisi et al, 1995;Hsieh et al, 2002). nucleotides presented by their O3' atoms.…”
Section: Setting Upmentioning
confidence: 99%
See 2 more Smart Citations
“…Without trans-activation, the polymerase produces primarily short transcripts and viral replication is disrupted 4, 5 . Extensive structural studies of TAR RNA have paved the way for the design of molecules to compete with the Tat protein in binding to the TAR element, thus inhibiting viral replication 3, 619 . However, to date none of these efforts have yielded leads with the potency and specificity required for successful clinical candidacy.…”
Section: Introductionmentioning
confidence: 99%